Variation of the refractive index by means of sulfate anion incorporation into nanoporous anodic aluminum oxide films - Minguez Bacho, Ignacio; Rodriguez-Lopez, S.; Climent-Font, Aurelio; Fichou, Denis; Vazquez, Manuel; Hernandez-Velez, M. (Microporous and Mesoporous Materials, 2016)
The variation in the refractive index of nanoporous anodic aluminum oxide (AAO) films regarding the sulfur anion incorporation is studied in this work. For this purpose, different samples are grown under potentiostatic conditions at different voltages and concentrations of sulfuric acid in the electrolyte. The samples are analyzed by Rutherford backscattering spectroscopy and infrared spectrometry, confirming the presence of sulfate anions and water embedded into the nanoporous MO films. The incorporation of. sulfate ions into the alumina matrix varies from 63 up to 11.7% regarding aluminum content. We have studied Fabry-Perot optical interferences by shining incident monochromatic light in specular reflectance conditions. The reflected monochromatic light waves interact in internal reflectivity generating constructive and destructive interferences known as Fabry-Perot optical interferences. An iterative method based on the equation for constructive interferences conditions in thin films and Snell equations is developed in order to calculate the refractive index of the nanoporous AAO films as a function of the wavelength. The calculated refractive indices increase when the sulfur content of the nanoporous MO films decreases. The variation of the calculated refractive index is 0.08 and remains constant in the wavelength range 400-1200 nm. (C) 2015 Elsevier Inc. All rights reserved.
Keywords: Nanoporous anodic alumina; Refractive index; Anion incorporation; Fabry-Perot interferences